Level of Financial Literacy Skills and Managerial Decision Implication among University Managers - Adewumi, Samson (International Review of Management and Marketing, 2024)
Poor managerial decisions on the part of university managers have continued to be on the increase due to poor financial literacy skills and knowledge. Previous studies on financial literacy skills in Nigeria have been largely investigated through the lens of financial institutions and small and medium-scale enterprises leaving sparse attention to the educational institution-university. This research chasm forms the need for this study. The paper aims to dissect the importance and challenges of financial literacy skills for managers’ financial and managerial decision-making. The methodological blueprint drew insight from the pragmatism philosophical worldview with a mixed-method approach to understanding the research problem. A total of 115 and 16-unit managers were randomly and purposively recruited with the structured questionnaire and semi-structured interview type employed to retrieve quantitative and qualitative data. Data were analyzed with the Structural Equation Model (SEM) and the NVivo (v.12) qualitative software. Financial planning, book-keeping, cashbook, and inventory financial literacy skills of managers were identified with accompanying challenges in the areas of lack of training on financial literacy development and poor financial skill and accounting background. The strategic measures required for the improved acquisition of financial literacy skills include timely financial literacy training, access to financial literacy tools and software, and the need to prioritize the recruitment of managers with financial literacy knowledge. The study echoes increased support for ensuring university managers are adequately trained on the complexities of financial literacy skills.